Hypervirulent Klebsiella pneumoniae in a South African tertiary hospital—Clinical profile, genetic determinants, and virulence in Caenorhabditis elegans - Dingiswayo, Likhona; Adelabu, Olusesan Adeyemi; Arko-Cobbah, Emmanuel; Pohl, Carolina; Mokoena, Nthabiseng Zelda; Du Plessis, Morne; Musoke, Jolly (Frontiers in Microbiology, 2024)
Introduction A distinct strain of Klebsiella pneumoniae (K. pneumoniae) referred to as hypervirulent (hvKp) is associated with invasive infections such as pyogenic liver abscess in young and healthy individuals. In South Africa, limited information about the prevalence and virulence of this hvKp strain is available. The aim of this study was to determine the prevalence of hvKp and virulence-associated factors in K. pneumoniae isolates from one of the largest tertiary hospitals in a South African province. Methods A total of 74 K. pneumoniae isolates were received from Pelonomi Tertiary Hospital National Health Laboratory Service (NHLS), Bloemfontein. Virulence-associated genes (rmpA, capsule serotype K1/K2, iroB and irp2) were screened using Polymerase Chain Reaction (PCR). The iutA (aerobactin transporter) gene was used as a primary biomarker of hvKp. The extracted DNAs were sequenced using the next-generation sequencing pipeline and the curated sequences were used for phylogeny analyses using appropriate bioinformatic tools. The virulence of hvKp vs. classical Klebsiella pneumoniae (cKp) was investigated using the Caenorhabditis elegans nematode model. Results Nine (12.2%) isolates were identified as hvKp. Moreover, hvKp was significantly (p < 0.05) more virulent in vivo in Caenorhabditis elegans relative to cKp. The virulence-associated genes [rmpA, iroB, hypermucoviscous phenotype (hmv) phenotype and capsule K1/K2] were significantly (p < 0.05) associated with hvKp. A homology search of the curated sequences revealed a high percentage of identity between 99.8 and 100% with other homologous iutA gene sequences of other hvKp in the GenBank. Conclusion Findings from this study confirm the presence of hvKp in a large tertiary hospital in central South Africa. However, the low prevalence and mild to moderate clinical presentation of infected patients suggest a marginal threat to public health. Further studies in different settings are required to establish the true potential impact of hvKp in developing countries.